2013
DOI: 10.1071/rj12074
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating livestock grazing to enhance native plant diversity and cover in native grasslands

Abstract: Temperate perennial grasslands globally have been subject to extensive biodiversity loss. Identifying livestock grazing regimes that maintain and enhance the diversity and cover of native plant species in these ecosystems remains a key challenge. The responses of vegetation to different sheep grazing regimes were assessed over 3 years in grasslands of southeastern Australia. An open communal experimental design was used to assess the effects of varying season and duration of exclusion of grazing by sheep, repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…In the Dambo wetlands of Zimbabwe, ungrazed wetlands had much lower species richness than both moderately grazed and year‐round grazing regimes (Dahwa et al ). Using various grazing exclusion trials in grasslands in southeastern Australia, Mavromihalis et al () recorded an overall loss of plant species richness coupled with an increase in herbage mass with complete exclusion of sheep but found little consistent changes in native species composition with other seasonal grazing exclusion treatments. A study of depressional wetlands in British Columbia, Canada, found differential responses of the plant community to grazing intensity depending on the type of wetland with a general increase in annual forbs and decrease in perennial herbaceous species with increasing intensity (Jones et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Dambo wetlands of Zimbabwe, ungrazed wetlands had much lower species richness than both moderately grazed and year‐round grazing regimes (Dahwa et al ). Using various grazing exclusion trials in grasslands in southeastern Australia, Mavromihalis et al () recorded an overall loss of plant species richness coupled with an increase in herbage mass with complete exclusion of sheep but found little consistent changes in native species composition with other seasonal grazing exclusion treatments. A study of depressional wetlands in British Columbia, Canada, found differential responses of the plant community to grazing intensity depending on the type of wetland with a general increase in annual forbs and decrease in perennial herbaceous species with increasing intensity (Jones et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of disturbance in maintaining biodiversity and ecosystem function is one of the most critical elements in the success of ecological restoration yet very few studies measure—let alone experimentally manipulate—disturbance regimes and track the impact on success of the restoration project (Fuhlendorf & Engle ; Suding ; Mavromihalis et al ). In fact, Brudvig () found that out of 190 articles on ecosystem restoration, only 17% measured the effects of disturbance on restoration outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although grazing rest during periods of peak plant growth and reproduction (i.e. spring) has been shown to maintain native forb richness and grass cover (Leonard & Kirkpatrick 2004;Zimmer et al 2010b;Mavromihalis et al 2013;Fedrigo et al 2018), this study could not dissociate the effects of grazing from other factors operating at larger spatial scales (i.e. rainfall).…”
Section: Discussionmentioning
confidence: 91%
“…; Mavromihalis et al . ; Fedrigo et al . ), this study could not dissociate the effects of grazing from other factors operating at larger spatial scales (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Animal grazing is the most dominant land use of grasslands (Mavromihalis et al 2013). Grazing influence on the relative abundance of C 4 plants has received much attention in the study of grasslands in North and South America (Reeder et al 2004;Altesor et al 2006;Derner et al 2006), Central Asia (Auerswald et al 2012;Ren et al 2012), South Africa (Franz-Odendaal et al 2002), Australia (Bell et al 2012) and New Zealand (Crush and Rowarth 2007).…”
Section: Introductionmentioning
confidence: 99%